2022
DOI: 10.3390/ijgi11030199
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Spectral Information of Sentinel-1 and Sentinel-2 Satellites for Above-Ground Biomass Retrieval of a Tropical Forest

Abstract: Earth Observation (EO) spectral indices have been an important tool for quantifying and monitoring forest biomass. Nevertheless, the selection of the bands and their combination is often realized based on preceding studies or generic assumptions. The current study investigates the relationship between satellite spectral information and the Above Ground Biomass (AGB) of a major private forest on the island of Java, Indonesia. Biomass-related traits from a total of 1517 trees were sampled in situ and their AGB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…The aboveground biomass model included species equations for temperate forests, making it easier to estimate fuel load [17,45,46]. The use of species equations combined with field data helps to reduce prediction bias [62]. Although the models allowed the prediction of the fuel load within the temperate forest ecosystem in Tamaulipas, it is advisable to carry out measurements to contrast the results obtained in this research.…”
Section: Discussionmentioning
confidence: 99%
“…The aboveground biomass model included species equations for temperate forests, making it easier to estimate fuel load [17,45,46]. The use of species equations combined with field data helps to reduce prediction bias [62]. Although the models allowed the prediction of the fuel load within the temperate forest ecosystem in Tamaulipas, it is advisable to carry out measurements to contrast the results obtained in this research.…”
Section: Discussionmentioning
confidence: 99%
“…All green plants strongly absorb visible electromagnetic radiation and reflect near-infrared radiation, and the spectral vegetation index emphasizes this difference by mathematically combining different spectral regions, which can represent the amount and condition of vegetation within a pixel [66]. Existing studies have used exhaustive methods to build vegetation indices to avoid the problems of existing vegetation indices ignoring important information that may be contained in other spectral bands and that different study areas and data producing different responses to different spectral bands [38]. It has been demonstrated that the weighting of the NIR band in the vegetation index affects the saturation point and that indices with higher weighting coefficients in the NIR band favor an increase in the sensitivity of the vegetation index [67].…”
Section: Establishment Of the Vegetation Index (Vi)mentioning
confidence: 99%
“…Dimitris Stratoulias used the spectral ratio of band 8 and band 2 of Sentinel-2 to obtain an R 2 of 0.70, while the best performing popular spectral index, EVI, achieved an R 2 of 0.65. The study found that a full wave combination survey of small-scale studies, which can make use of current satellite systems to obtain amplified information and avoid assumptions about environmental, structural, and ecosystem characteristics for the selection of the vegetation index, can provide stronger correlations and more accurate results than the blind application of popular spectral indices [38].…”
Section: Introductionmentioning
confidence: 99%
“…Jue Xiao et al and Nichol et al used the texture features to further improve the accuracy of AGB inversion from remote sensing images [18,19]. However, passive optical remote sensing images are unable to obtain vertical structural information of trees and are limited by the influence of cloud cover at the time of observation [20]. These limitations would result in the generally low accuracy of AGB estimation, especially in the dense vegetation areas with high biomass for the image spectra have a strong saturation effect and tend to lose sensitivity [21][22][23].…”
Section: Introductionmentioning
confidence: 99%